Effect of sustained virologic response on liver-related mortality among individuals living with hepatitis C by treatment era: A population-based retrospective cohort study - Aysegul Erman; Karl Everett; William W. L. Wong; Farinaz Forouzannia; Christina Greenaway; Naveed Janjua; Jeffrey C. Kwong; Beate Sander (PLoS ONE, 2025)
Purpose Sustained virologic response (SVR) is a validated surrogate marker for successful hepatitis C virus (HCV) treatment. Historically, interferon-based therapies, the standard of care for decades, offered only limited efficacy with respect to SVR. The recent introduction of highly effective direct-acting antivirals (DAAs) revolutionised treatment, expanding treatment eligibility among individuals with advanced liver disease (ALD) and drug/alcohol-related substance use disorder. Given these clinical policy shifts, we assessed the real-world impact of SVR on liver-related death for these key clinical groups for whom treatment had previously been less feasible. Methods We conducted a population-based, cohort study of Ontario residents with HCV viremia between January 1st, 1999, and December 31st, 2018, with follow-up to May 31st, 2021 (N = 73,411) and used cause-specific hazard models to explore the association between SVR and liver-related death. Results SVR was associated with a significant reduction in liver-related deaths (adjusted hazard ratio [aHR]: 0.22, 95%CI: 0.20–0.24). This benefit was consistent across all levels of liver disease severity, including individuals with (aHR: 0.11, 95%CI: 0.06–0.18) and without (aHR: 0.13, 95%CI: 0.10–0.17) cirrhosis, individuals with ALD (aHR: 0.24, 95%CI: 0.22–0.27) as well as among individuals with (aHR: 0.24, 95%CI: 0.21–0.27) and without (aHR: 0.21, 95%CI: 0.18–0.24) substance use disorder. Conclusions This study demonstrates the real-world impact of SVR on liver-related mortality and highlights the value of early treatment and continued support for populations who are marginalised.